The Development of Nur El-Falah Islamic Boarding School in Kubang Village, Petir Subdistrict, Serang Regency, 1989–2015 - Dego Setiawan; Tubagus Umar Syarif Hadi Wibowo; Rikza Fauzan (UNIVERSITAS MUHAMMADIYAH METRO, 2027)
This research aims to explain the development of the Nu El-Falah Islamic Boarding School from 1989-2015: 1) the history of the establishment and profile of the Nur El-Falah Islamic Boarding School, 2) the development of the Nur El-Falah Islamic Boarding School from 1989-2015, 3) the role Nur El-Falah Islamic Boarding School as an Islamic Education Institution. The method used in this study is the historical research method consisting of heuristics, criticism, interpretation, and historiography. The Nur El-Falah Islamic Boarding School was established at the suggestion of teacher K.H Abdul Kabier, who advised him to build an educational institution in his hometown. After that, K.H Abdul Kabier opened a formal school, namely the Muamilin School, to produce teachers. During the leadership of K.H Idy Faridy Hakim, he was able to build and raise the name of the Islamic Boarding School both in terms of its construction and attracting students because of its charisma and authority. As an Islamic educational institution, Pondok Pesantren Nur El-Falah continues to improve its quality starting from the curriculum, teachers and also provides facilities that can make students independent.